Early phenology and growth trait variation in closely related European pine species. Issue 1 (3rd December 2017) - Wachowiak, Witold; Perry, Annika; Donnelly, Kevin; Cavers, Stephen
Abstract: Closely related taxa occupying different environments are valuable systems for studying evolution. In this study, we examined differences in early phenology (bud set, bud burst) and early growth in a common garden trial of closely related pine species: Pinus sylvestris, P. mugo, and P. uncinata . Seeds for the trial were sourced from populations across the ranges of each species in Europe. Over first 4 years of development, clear differences were observed between species, while the most significant intraspecific differentiation was observed among plants from P. sylvestris populations from continental European locations. Trait differences within P. sylvestris were highly correlated with altitude and latitude of the site of origin. Meanwhile, P. mugo populations from the Carpathians had the earliest bud set and bud flush compared to other populations of the species. Overall, populations from the P. mugo complex from heterogeneous mountain environments and P. sylvestris from the Scottish Highlands showed the highest within‐population variation for the focal traits. Although the three species have been shown to be genetically highly similar, this study reveals large differences in key adaptive traits both among and within species. Abstract : The study reveals large differences in key adaptive traits both among and within closely related and genetically uniform pine species. Patterns of phenotypic variation indicate that selection has operated in distinct ways in different parts of the species distribution, suggesting variation in the primary drivers of selection.